The moderating role of spirituality and gender in Canadian and Iranian emerging adolescents’ theory of mind and prosocial behavior - Khalili, Nadia; Bosacki, Sandra; Talwar, Victoria (Frontiers in Psychology, 2023)
While research has found a link between ToM and spirituality in terms of caring and helping others which may also vary across cultures, the moderating role of spirituality and culture of these associations in emerging adolescence has received little attention. The current study empirically the role of spirituality and culture in relation to ToM and prosocial behaviour in Canadian and Iranian emerging adolescents. A total of 300 (160 girls) emerging adolescents (M=11.502, SD=2.228) were recruited from Montreal, Canada and Karaj, Iran. A double moderation analysis was conducted, and results indicated nonlinear relationships between culture, spirituality, ToM, and prosocial behaviour. A higher level of spirituality indicated a strong negative influence on ToM and prosocial behaviour for all subjects. However, low and middle levels of spirituality differed by culture. Implications for youth’s social-emotional understanding will be discussed.